Theme-Based Edupreneurship Model for Reading Achievement and Learner Autonomy - Asti Veto Mortini; Sri Wuli Fitriati; Rahayu Puji Haryanti; Sri Wahyuni; Juan Carlos Rodriguez (Pandawan, 2026)
This study examines the effectiveness of a Theme-Based Learning Model within an edupreneurship framework to improve students’ reading achievement and learning independence. A mixed-method triangulation design was applied, combining quantitative data from pre- and post-tests and questionnaires with qualitative insights from student interviews. The participants were third-semester English education students categorized into four VARK learning styles: visual, auditory, reading/writing, and kinesthetic. Results indicate that all learning style groups experienced an improvement in reading achievement after the implementation of theme-based learning. Auditory and visual learners showed the most significant progress, while kinesthetic learners demonstrated moderate improvement. Questionnaire and interview findings further reveal that the model promotes learning independence, with visual learners exhibiting the highest level of autonomous learning behaviors. The integration of thematic content made learning more engaging and contextual, allowing students to connect reading activities with real-world scenarios, fostering critical thinking and creativity two essential competencies in edupreneurship. The study concludes that the Theme-Based Learning Model serves as an effective instructional approach that simultaneously enhances academic performance and cultivates independent learning. These findings provide valuable insights for educators and curriculum designers in integrating reading instruction with entrepreneurial oriented learning practices. The model is recommended for broader implementation across courses or institutions, as it aligns with 21st-century education goals by supporting student-centered learning, innovation, and lifelong learning.